Financial Innovations and Profitability of Commercial Banks in Uganda - Atukunda, Gershom; Musiita, Benjamin; Atwiine, Johnson; Atwine, Aquilionus; Olyanga, Anthony Moni (Journal of Economics and Behavioral Studies, 2024)
The purpose of this study was to examine the relationships between financial innovation and profitability of commercial Banks in Uganda. The study was prompted by the low profitability evidenced by some banks being closed down because of low profitability. The study adopted a cross-section and descriptive research design using Roscoe 1975 to get a sample size of 24 commercial banks. Self-administered questionnaires were used to collect the responses. Based on the goals of the study, the data was examined for validity and reliability, examined using SPSS, and the results were reported. The results showed that the profitability of commercial banks in Uganda had a positive and significant association with both process and product innovation, suggesting that improving one will benefit the other. However, product innovation was found to be a stronger predictor of profitability in commercial Banks in Uganda. With these findings, the study contributes to providing empirical evidence that financial innovation in commercial banks is highly influenced by commercial banks introducing and improving their products/services since it results in profitability. There is also a need to put much emphasis on Financial Innovations by continuously introducing and improving on the existing products/services. The Commercial Banks in Uganda should promote and appreciate Financial Innovations as they are vital not only in enhancing cost minimization, thus improving profitability